Marginal discrepancy and retention post-cementation of unretentive crowns in conometric systems: An in vitro comparative study - Al-Chalabi , Zainab S; Tuna , Süleyman H (Journal of Baghdad College of Dentistry, 2025)
Background: This in vitro study was carried out to determine the marginal discrepancy (MD) and retention force (RF) values in the conometric systems (CSs) having poor retention after cementation using two distinct cements and procedures. Materials and methods: This study used 24 monolithic zirconia crowns that were cemented into 24 conometric caps and 24 conometric abutments attached to implant analogues. The researchers repeated the pull-out test until they achieved the RF values